Kebijakan Formulasi Penegakan Hukum terhadap Tindak Pidana Perdagangan Orang Berdasarkan Undang-Undang Nomor 21 Tahun 2007 - Muhammad Islahuddin; Ahmad Nabiel Syahbana (Lembaga Yasin AlSys, 2025)
This study explores the handling of human trafficking crimes in Indonesia from a legal perspective, with a particular focus on the application of Article 2 paragraph (1) of Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking as the primary legal basis for addressing such cases. The research adopts a normative juridical approach and qualitative analysis of secondary data, including regulations, government policies, and law enforcement practices. The findings indicate that, although the legal framework is comprehensive, its implementation faces multiple challenges. These include limited understanding among law enforcement officials regarding the legal substance, victim handling procedures, and the identification of exploitation forms based on human rights principles. Additionally, resource constraints, weak inter-agency coordination, and low public legal awareness further undermine the effectiveness of law enforcement. Legal protection for victims also remains suboptimal in ensuring substantive justice. Therefore, enhancing the capacity of law enforcement, strengthening cross-sectoral coordination, and promoting public awareness and empowerment are strategic measures necessary for more effective and equitable prevention and handling of human trafficking.